Comparative Analysis of Freemium Policies and Procedure between Major Mobile Platforms - Muhamad Idaham, Umar Ong; Imran Edzereiq, Kamarudin; M. A., Ameedeen (IEEE, 2014)
Smartphone ownership is fast becoming a birth-right in the world of to-day. For developers, this opens up a whole new world of business opportunities where applications are being purchased every single day. Besides the multi billions of dol-lars spent each year on application purchases alone, consumers nowadays are facing an even newer trend; In-App Purchasing. In-App purchasing refers to a scenario where the initial applications are downloadable for free, however some additional functions or elements of the applications may be acquired within the applications for a small (or not so small) fee. This paper aims to review this trend and the guidelines that is applied to this phenomenon by the three main smartphone operating systems; iOS, Android and Windows. This would be done by highlighting the major strengths and weaknesses that each platform has to offer, as well as the common policies that are enforced across all three platforms.